Methods for the physical characterization and quantification of extracellular vesicles in biological samples - Rupert, Déborah L.M.; Claudio, Virginia; Lässer, Cecilia; Bally, Marta (Biochimica et biophysica acta. General subjects, 2017)
Our body fluids contain a multitude of cell-derived vesicles, secreted by most cell types, commonly referred to as extracellular vesicles. They have attracted considerable attention for their function as intercellular communication vehicles in a broad range of physiological processes and pathological conditions. Extracellular vesicles and especially the smallest type, exosomes, have also generated a lot of excitement in view of their potential as disease biomarkers or as carriers for drug delivery. In this context, state-of-the-art techniques capable of comprehensively characterizing vesicles in biological fluids are urgently needed. This review presents the arsenal of techniques available for quantification and characterization of physical properties of extracellular vesicles, summarizes their working principles, discusses their advantages and limitations and further illustrates their implementation in extracellular vesicle research. The small size and physicochemical heterogeneity of extracellular vesicles make their physical characterization and quantification an extremely challenging task. Currently, structure, size, buoyant density, optical properties and zeta potential have most commonly been studied. The concentration of vesicles in suspension can be expressed in terms of biomolecular or particle content depending on the method at hand. In addition, common quantification methods may either provide a direct quantitative measurement of vesicle concentration or solely allow for relative comparison between samples. The combination of complementary methods capable of detecting, characterizing and quantifying extracellular vesicles at a single particle level promises to provide new exciting insights into their modes of action and to reveal the existence of vesicle subpopulations fulfilling key biological tasks. [Display omitted] •Characterizing exosomes is challenging due to their physicochemical heterogeneity.•We present state-of-the-art methods to characterize and quantify vesicle samples.•Physical properties discussed include size, density, optical properties and charge.•Vesicle concentration is expressed in biomolecular content, particle number or mass.•Profiling of extracellular vesicles requires complementary characterization tools.